Aesthetic Concept - Choreography of Piso Surit Dance in Karo Community - Adlin, Dilinar (BIRCU, 2020)
Piso Surit dance in Karo community has distinctive characteristics in its movement techniques, floor patterns, environmental ethical norms, and symbolic-philosophical images. All of these characteristics grow and develop in line with aspects of the living environment that have been integrated in each form of art. This study aims to explain: 1) the basis and rules of Piso Surit dance; and 2) the concept of Â Piso Surit dance choreography. This study uses a choreographic-anthropological approach, which is to analyze the relationship of dance motion with the aesthetic choreographic concept of Piso Surit dance and Karo community's mindset. Observation, documentation, and interview techniques are used to collect data and then the triangulation data analysis process is carried out to obtain the credibility of the data. The results showed that the rules for the use and application of motive motives fall into two categories, namely for male dancers and female dancers. The application of the prevailing floor pattern is dealing with their partners, side by side, and encircling each other. The rules for the use and application of accompaniment patterns intend to create a unified nature that is subtle, gentle, and harmonious. In the concept of choreography, Piso Surit's dance movements are broken down into nine (9) sections. The movements use techniques such as: a) tiptoeing, b) rotating movements, c) stopping fingers, and d) up and down movements. The music used as accompaniment in the Piso Surit dance is a folk song in Karo area with the same title. This dance uses 'beautiful' make-up to emphasize the dancer's facial lines in a dance performance, while the fashion is a dress code as used by Karo community. As a pair dance, the floor pattern applied is to show or emphasize the story of how young Karo young people combine love.